PESANTREN NAWESEA MENJADI UNIVERSITAS KELAS DUNIA PEMIKIRAN YUDIAN WAHYUDI - Akso, Akso; Sadari, Sadari (Moderation | Journal of Islamic Studies Review, 2022)
This article is to explain how to reform Islamic boarding schools towards the era of industrialization in Yudian Wahyudi's thought. The analysis in this article uses a qualitative method with a naturalistic paradigm, namely research that aims to describe and find novelties in order to answer the challenges of globalization in the Nawesea Islamic boarding school in Yogyakarta as the object of research. Pesantren education has been over-specialized and over-produced by deepening its religion on attafaqquh fiddin (studying religion). For this reason, in responding to the challenges of globalization, pesantren must move to seek knowledge from the fardu ain and then to the fardu kifayah. So that the potential of students is not cut off, in the future students will not only be able to study religion, but will be able to master general sciences. This is implied in the meaning of the hadith that the ulama (plural of alim) are the heirs of anbiya '(plural of the word prophet). It is hoped that in the future students will inherit one of Noah's legacy of expertise and miracles, namely the shipping sector, inherit one of the skills and miracles of the Prophet Yusuf, namely the field of Economics, inherit one of the skills and miracles of Prophet Dawud, namely the field of iron technology, inherit one of the skills and miracles of Prophet Sulaiman, namely communication (lingua franca) of contemporary civilization, inheriting the expertise and other miracles of Prophet Solomon, namely the field of Management, inheriting one of the skills of Prophet Isa, namely the field of Medicine. To become the world's best university, it took Harvard nearly 4 (four) centuries. Likewise, the Nawesea Islamic boarding school certainly needs a long time to change Sunan Averroes into Harfard, history will answer.